Analisis Fabrikasi Desain Passive Mixing Microchannel Perangkat Mikrofluidik Material Acrylic Dengan Laser CO2 Daya Rendah - Badruzzaman Badruzzaman; Ario Sunar Baskoro (Jurnal Teknologi Terapan, 2016)
Microfluidics devices have been applied in the biomedical field to manipulate the tissue fluids in channels with dimensions between 5-500 lm. Microfluidics device manufactured by a microfabrication process consisting of design, microstucturing and back-end processes. One application of microfluidics is a passive mixing microchannel. In this device, the liquid will flow through the channel without any moving parts and the pressure from the outside to produce a fluid mixing. It is important to design the shape of the channel to generate a nice passive mixing microchannel. Low power CO2 laser is used to process microstucturing as cutting tools to produce microfluidic devices on acyilic material. Surface roughness lines were designed to be observed. In this study, the design process channel carried by the experimental method through the parameters that affect the output of the process is the power of laser cutting, cutting speed and design channel. And then the fabrication of microfluidics with back-end processing is done by the process of merging with a thermal bonding method. Finally, From the experimental results, the design of the channel 1 has an influence on all the parameters for surface roughness compared with a channel design 2.